ANALISIS EFEKTIVITAS SISTEM INFORMASI AKUNTANSI DAN PENGENDALIAN INTERNAL PERKREDITAN PADA PT. BANK PEMBANGUNAN DAERAH PAPUA CABANG MANADO - Krar, Sonaria; Tinangon, Jantje J.; Gamaliel, Hendrik (GOING CONCERN : JURNAL RISET AKUNTANSI, 2018)
A good Accounting Information System can help company to provide the company’s need for other information related to busyness process that exist within the company. This research study at PT. Regional bank development papua branch manado.This study aims to know effectiveness of information accounting system and internal control of kredit on PT.regional bank development papua branch manado.This study used a deskriptive qualitative method is a method that is done by classifying data and inormation which is obtained by various technicques such as survey, interviews, and others. So get a relevant conclusion.The results of the analysis of the conclusion that the information system and internal control of PT. bank Papua manado branch has been running well, and in accordance with procedures that have been set by the bank indonesian. Allready meet the characteristics and elements of internal control. Keywords : Information Accounting System, Internal control, Credit.